Fertilizer use soil health and agricultural sustainability - Krasilnikov, Pavel; Taboada, Miguel Angel; Amanullah (MDPI, 2022)
Due to the growing population and consequent pressure of use, agricultural soils must maintain adequate levels of quantity and quality to produce food, fiber, and energy, without falling victim to a negative impact on their balance of nutrients, health, or their ability to function. The use of mineral fertilizers has long been a key tool to offset nutrient outputs and thus achieve increased yields [1–4]. Fertilizer application is believed to have been responsible for at least 50% increase in crop yield in the 20th century [5,6]. According to [5], average corn yields would decline by 40 percent without nitrogen (N) fertilizer application, while long-term studies confirmed a 40–57 percent yield decline in wheat without fertilizer application. Yousaf et al. [6] reported a 19–41% yield increase in rice, and a 61–76% increase in rapeseed with the combined application of NPK fertilizers. However, due to the inappropriate use of mineral fertilizers (i.e., when used in both excess or deficiency), mostly concerning nitrogenous and phosphate, many productive soils have been thwarted in their ability to function, as shown not only by chemical indicators but also by physical and biological ones. Thus, improper fertilizing technology might have a negative effect on soil health and soil-related ecosystem services. Imbalanced use of chemical fertilizers can alter soil pH, and increase pests attack, acidification, and soil crust, which results in a decrease in soil organic carbon and useful organisms, stunting plant growth and yield, and even leading to the emission of greenhouse gases [7,8]. Soil health is defined as the capacity of soil to function as a vital living system, within ecosystem and land-use boundaries, to sustain plant and animal health and productivity, and maintain or improve water and air quality. A major challenge for agricultural sustainability is to conserve ecosystem service delivery while optimizing agricultural yields. This Special Issue addresses the task to find a balance between increasing yields using conventional and novel fertilizers, and the maintenance of soil and environmental health as a basis for the sustainable intensification of the agricultural sector. The purpose of this issue was to provide new knowledge on fertilizer use, soil health, and agricultural sustainability. We received a total of 13 papers that provided interesting and innovative information. Five of them [9–13] were works on basic studies on the status of nutrients. These studies were based on the reviews of published works, or on experiments under controlled conditions (greenhouse and incubation) referring to nitrogen losses due to volatilization, leaching, denitrification, the distribution of nutrients, the combined or integrated use of mineral and organic fertilizers, bio-based nitrogen, or new findings in sulfur, a largely low-attended nutrient.